Inhibition of Rehmannia mosaic virus Infection by Ganoderma sp. Extract - Mustika Ajeng Kartini Putri Pertiwi; Suryanti Suryanti; Susamto Somowiyarjo (Universitas Gadjah Mada, 2020)
In fruiting bodies and mycelia of several fungi belonging to a Basidiomycetes group, among others, Ganoderma contains active polysaccharides and has potential as an antiviral substances. This study aimed to determine the effect of mycelium and fruiting body extract of Ganoderma sp. against Rehmannia mosaic virus (ReMV) infections on Chenopodium amaranticolor with variations of dilution and application times. The results showed that mycelium and fruiting body extract of Ganoderma sp. could inhibit ReMV infections. Antiviral extract which were applied 4 hours before, and at the same time with virus inoculation resulted in a higher viral inhibition rates than when applied 4 hours after virus inoculation. Fruiting body extract at 10-1 and 10-2 dilutions delayed symptom appearance caused by ReMV infection when applied 4 hours before virus inoculation. Mycelium extract at dilution of 10-2 and 10-3 applied 4 hours before virus inoculation resulted in the highest inhibition rate (100%) which was indicated as the number of local lesions on Chenopodium amaranticolor leaves. Meanwhile the fruiting body extract dilution of 10-1 resulted in highest inhibition (99.55%) when applied 4 hours before virus inoculation.